Plain Patterns: Threads of Hope - Gould, Leslie, 1962- (Thorndike, Maine : Center Point Large Print, 2022)
"Tally Smuckers quiet life of reading and quilting hides her sorrow over her mothers declining health and the lack of a fulfilling future for herself. When her daily life is shaken by her free-spirited neighbor Danielle - who grew up Plain but joined the Army at eighteen - Tallys instinct is to distance herself. Yet she finds she cant turn away when Danielles brother, Kenan, specifically asks for her help. She invites Danielle to visit Plain Patterns quilt shop with her, where the story of the plight of a WWI soldier and the girl he left behind resonates with both Tally and Danielle, but for different reasons. When Tallys mother suffers a setback at the same time Danielles PTSD becomes unmanageable, it seems Tallys efforts to aid them only makes things worse. Can the soldiers story, along with the care of Kenan, help Tally accept the hope that waits just around the corner?"- -
Keywords: Amish -- Fiction; Quilts -- Fiction; Post-traumatic stress disorder -- Patients; Fiction; Indiana -- Fiction; Christian fiction